Local endemism and within‐island diversification of shrews illustrate the importance of speciation in building Sundaland mammal diversity. Issue 20 (12th September 2016) - Demos, Terrence C.; Achmadi, Anang S.; Giarla, Thomas C.; Handika, Heru; Maharadatunkamsi,; Rowe, Kevin C.; Esselstyn, Jacob A.
Abstract: Island systems are important models for evolutionary biology because they provide convenient, discrete biogeographic units of study. Continental islands with a history of intermittent dry land connections confound the discrete definitions of islands and have led zoologists to predict (i) little differentiation of terrestrial organisms among continental shelf islands and (ii) extinction, rather than speciation, to be the main cause of differences in community composition among islands. However, few continental island systems have been subjected to well‐sampled phylogeographic studies, leaving these biogeographic assumptions of connectivity largely untested. We analysed nine unlinked loci from shrews of the genus Crocidura from seven mountains and two lowland localities on the Sundaic continental shelf islands of Sumatra and Java. Coalescent species delimitation strongly supported all currently recognized Crocidura species from Sumatra (six species) and Java (five species), as well as one undescribed species endemic to each island. We find that nearly all species of Crocidura in the region are endemic to a single island and several of these have their closest relative(s) on the same island. Intra‐island genetic divergence among allopatric, conspecific populations is often substantial, perhaps indicating species‐level diversity remains underestimated. One recent (Pleistocene) speciation event generated two morphologically distinct, syntopic species on Java, further highlighting the prevalence of within‐island diversification. Our results suggest that both between‐ and within‐island speciation processes generated local endemism in Sundaland, supplementing the traditional view that the region's fauna is relictual and primarily governed by extinction.